2014
DOI: 10.1111/1745-9133.12094
|View full text |Cite
|
Sign up to set email alerts
|

Paying Restitution: Experimental Analysis of the Effects of Information and Rationale

Abstract: Research SummaryMost crime victims do not receive the restitution they are owed. This study is an experiment that addresses two reasons offenders give for why they do not pay their court-ordered restitution: (a) lack of understanding of how much they owe and where their payments are directed and (b) a belief that the sanctions are unfair. A total of 771 offenders were randomly assigned to one of four conditions in a 2 × 2 between-subjects design in which, over a 6-month period, three quarters of the offenders … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(37 citation statements)
references
References 51 publications
1
36
0
Order By: Relevance
“…In contrast to the Information Only Condition, results from the Ruback et al. () experiment indicated that the Rationale Only, the Rationale and Information, and Control Conditions failed to increase either the amount or the number of payments. Thus, there was, presumably, no change in self‐perception.…”
Section: Prior Experimentsmentioning
confidence: 94%
See 4 more Smart Citations
“…In contrast to the Information Only Condition, results from the Ruback et al. () experiment indicated that the Rationale Only, the Rationale and Information, and Control Conditions failed to increase either the amount or the number of payments. Thus, there was, presumably, no change in self‐perception.…”
Section: Prior Experimentsmentioning
confidence: 94%
“…The data for this study came from three sources: (1) the prior experiment, in which 775 individuals were randomly assigned to different conditions designed to motivate payment of restitution (Ruback et al., ); (2) a survey completed by 128 of these individuals 1.5 years after the experiment ended (Gladfelter, Lantz, and Ruback, ); and (3) data from the Pennsylvania State Police regarding arrests after the experiment. All three data collection efforts had been approved by the university institutional review board.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations